Poverty Alleviation Strategy: Challenges and Opportunities in Realizing SDGs in Indonesia - Marta Ayu Saputri; Millah, Mazida Nurul; Reza Nurul Falah; Siska Afiyati Dewi (IAIN Madura, 2025)
The poverty rate in Indonesia reaches 24.06 million people out of a total population of 280 million. Various influencing factors include, for example, the still low quality of education. This study discusses the challenges, opportunities, and strategies for poverty alleviation in Indonesia within the context of achieving the Sustainable Development Goals (SDGs), particularly the first goal: